Diagnostic accuracy and safety of 16α-[18F]fluoro-17β-oestradiol PET-CT for the assessment of oestrogen receptor status in recurrent or metastatic lesions in patients with breast cancer: a prospective cohort study. Issue 4 (April 2019) - Chae, Sun Young; Ahn, Sei Hyun; Kim, Sung-Bae; Han, Sangwon; Lee, Suk Hyun; Oh, Seung Jun; Lee, Sang Ju; Kim, Hee Jeong; Ko, Beom Seok; Lee, Jong Won; Son, Byung Ho; Kim, Jisun; et al.
Summary: Background: A biopsy of first recurrence or metastatic disease is recommended to re-evaluate oestrogen receptor status in patients with breast cancer and to select appropriate treatment. However, retesting for oestrogen receptor status with rebiopsy is not always feasible, depending on lesion location and the risk associated with biopsy, and in these cases clinicians continue to treat patients according to the oestrogen receptor status of the primary tumour. Consequently suboptimal therapy might be offered to these patients. We assessed the diagnostic accuracy and safety of 16α-[ 18 F]fluoro-17β-oestradiol ( 18 F-FES) PET-CT to assess oestrogen receptor status in patients with recurrent or metastatic breast cancer. Methods: We did a prospective cohort study at the Asan Medical Center, Seoul, South Korea. Eligible patients had breast cancer, with first recurrence or metastatic disease at presentation, were 19 years or older, and had an Eastern Cooperative Oncology Group performance status of 0–2. The primary objective was to show the agreement between qualitative 18 F-FES PET-CT interpretation and the results of oestrogen receptor expression by immunohistochemical assay, a non-reference standard test. Whole-body 18 F-FES PET-CT imaging was done after intravenous injection of 111–222 MBq of 18 F-FES, with dosing primarily determined by radiation dosimetry analysis. 18 F-FES uptake above background intensity was interpreted as positive. Efficacy was assessed in all patients with histologically confirmed recurrent or metastatic breast cancer who received 18 F-FES and had PET-CT images available (intention-to-diagnose analysis), and safety was assessed in all patients who received 18 F-FES. This study is registered withClinicalTrials.gov, numberNCT01986569 . Findings: Between Nov 27, 2013, and Nov 10, 2016, 93 patients were enrolled. Of the 85 patients included in the efficacy analysis, 47 (55%) were oestrogen receptor-positive and 38 (45%) were oestrogen receptor-negative. Positive status percent agreement between the 18 F-FES PET-CT results and oestrogen receptor status by immunohistochemical assay was 76·6% (95% CI 62·0–87·7) and the negative status percent agreement was 100·0% (90·8–100·0). Patients who were oestrogen receptor-positive and had a positive 18 F-FES PET-CT result had a significantly higher progesterone receptor expression than those who were oestrogen receptor-positive and had a negative 18 F-FES PET-CT result (23 [68%] of 34 patients vs 0 of 11 patients; p<0·0001). The most common adverse event was procedural pain in nine (10%) of 90 patients injected with 18 F-FES. No adverse events were related to the study drug except injection site pain in one (1%) patient. No serious adverse events were recorded. Interpretation: The high negative percent agreement between 18 F-FES PET-CT and oestrogen receptor status by immunohistochemical assay in this cohort suggests that positive 18 F-FES uptake by recurrent or metastatic oestrogen receptor-positive breast cancer lesions could be an alternative to oestrogen receptor assays in this setting. Staging assessment should include 18 F-FES PET-CT when retesting oestrogen receptor status is not feasible. Funding: Asan Institute for Life Sciences, Ministry of Health and Welfare, South Korea.